The effect of stem and stem-based robotic activities on the development of students’ perceptions of mental risk-taking and its predictors and their inquiry skills in science learning - AKKOYUN, Nida; YALCIN, Sema ALTUN; CAKIR, Zehra; YALCIN, Pasa (Asian Journal of Contemporary Education, 2023)
The research explores the effect of STEM and STEM-based robotic activities on the development of students’ perceptions of mental risk-taking and its predictors and their perceptions of inquiry learning skills related to science. A mixed method was applied in the research. Its sample consisted of 35 students in a high school of the Ministry of National Education in a medium-scale province of the Eastern Anatolia Region between the 2017-2018 educational year. The Scale for Perceptions of Mental Risk-taking in Science Learning and Its Predictors (SPMRSLIP) and the Scale for Perception of Inquiry Learning Skills for Science (SPILSS) were applied to obtain the quantitative data in the research. In addition, the focus group interview was held. The STEM and STEM-based robotic activities have been performed with the students for 14 weeks. In the findings obtained at the end of the research, no significant difference was determined between the perception pre-test and post-test scores related to mental risk-taking and its predictors in science learning. However, difference was found in the dimension of interest. It was found that there was a significant difference between the pre-test and post-test scores in the inquiry learning skills perception scale for science and the qualitative findings also supported this result. According to the results, it can be recommended that STEM and Robotic educations should be given in other grades.